Null mutations in the alpha PS2 and beta PS integrin subunit genes have distinct phenotypes. - Brown, N.H. (Development, 1994)
The two Drosophila position-specific (PS) integrins are expressed on complementary sides of sites where different cell layers adhere to each other, such as the attachments of the embryonic muscles to the epidermis. While there is suggestive evidence that the PS integrin-mediated adhesion is via the extracellular matrix, it is also possible that it occurs through the direct interaction of the two integrins, alpha PS1 beta PS and alpha PS2 beta PS. To help distinguish between these possibilities a comparison between the phenotypes caused by the absence of the beta PS subunit and the absence of one of the PS alpha subunits, alpha PS2, has been made. Two pieces of evidence are provided that prove that the alpha PS2 subunit is encoded by the locus inflated (if). Firstly, three new if alleles have been isolated, each of which is associated with a molecular lesion in the alpha PS2 gene, and each of which results in the complete loss of if activity. Secondly, a 39 kb fragment of genomic DNA that encompasses the alpha PS2 gene completely rescues if mutations when introduced into the germline by P-element-mediated transformation. A comparison of the null inflated phenotype with that of the locus that encodes the beta PS subunit, myospheroid (mys), reveals that while the beta PS subunit is required for the adhesion of the epidermis along the dorsal midline, the alpha PS2 subunit is not. In if mutant embryos, the muscles remain attached to the other cell layers significantly longer than in a mys mutant embryo. This shows that the alpha PS2 beta PS integrin only contributes part of the adhesive activity at the sites of PS integrin adhesion, and rules out a model where PS integrin function occurs solely by the direct interaction of the two PS integrins.